The Anatomy of Leadership in Industry 4.0 : The 4.0D® Leadership Development Model. - Uys, Johann; Webber-Youngman, Ronny (London : Knowledge Resources, 2021)
With the large-scale advent of the 4th Industrial Revolution (4IR), the world is in constant flux. This has been exacerbated by the fallout of Covid-19. To be relevant in the next few decades, any business that wants to develop their leadership cadres will have to embrace drastic transformations in their approach to every area of leadership formalisation, modelling, training and development._x000D__x000D_This newly developed 4.OD® Leadership Development Model is the departure point for business to embark on new leadership journeys appropriate for the future. The new leadership skills required are comprehensively addressed._x000D_The model will become one of the main contributors in the field of future business leadership and leadership preparedness for Industry 4.0 for most organisations._x000D__x000D_4.OD® Leadership Development Model is scientifically based within the context of organisations and business._x000D_The Anatomy of Leadership in Industry 4.0 is a detailed exposition of the model, the technical and dynamic aspects of the model application as well as the implications for leadership in business.
Front-Cover -- Copyright -- FOREWORD -- PREFACE -- PREAMBLE -- CHAPTER 1: INTRODUCTION -- THE 4.0D® LEADERSHIP DEVELOPMENT MODEL -- LEADERSHIP MISCONCEPTIONS -- THE PRINCIPLE OF A JOURNEY -- THE "WHY" BEHIND THE 4.0D® LEADERSHIP DEVELOPMENT MODEL -- CHAPTER 2: AN OVERVIEW OF LEADERSHIP THEORY -- INTRODUCTION -- DIVINE RULE -- "GREAT MAN" THEORIES (1840's) -- TRAIT THEORIES (1930's-1940's) -- BEHAVIOURAL THEORIES (1940's TO EARLY 1960's) -- CONTINGENCY THEORY OF LEADERSHIP (1960's-1970's) -- SITUATIONAL THEORIES (1970's-1980's) -- TRANSFORMATIONAL THEORIES (1980's) -- EMOTIONAL INTELLIGENCE (1990's) -- CONCLUDING REMARKS -- CHAPTER 3: LEADERSHIP, THE 4IR AND BEYOND -- INTRODUCTION -- A HISTORICAL OVERVIEW OF THE INTERFACE BETWEEN TECHNOLOGY AND LEADERSHIP -- A HOLISTIC OVERVIEW OF THE ECONOMIC CONTEXTS PRECEDING THE INDUSTRIAL REVOLUTIONS -- 4IR TECHNOLOGIES -- SKILLS REQUIRED IN THE 4IR -- LEADERSHIP CHALLENGES AND THE FUTURE IN THE 4IR AND BEYOND -- THE FIFTH INDUSTRIAL REVOLUTION -- CONCLUDING REMARKS -- CHAPTER 4: FORMULATING THE 4.0D® LEADERSHIPDEVELOPMENT MODEL: THE THINKING BEHIND THE THINKING -- INTRODUCTION -- START WITH WHY -- WEIGHING UP THE OPTIONS: THE ESSENSCE OF THE PILLARS OF THE 4.0D® LEADERSHIP DEVELOPMENT MODEL -- THE THREE-PART MIND -- CONCLUDING REMARKS -- CHAPTER 5: The 4.0D® LEADERSHIP DEVELOPMENT MODEL -- INTRODUCTION -- THE DIMENSIONS AND ELEMENTS OF THE 4.0D® LEADERSHIP DEVELOPMENT MODEL -- PERTINENT POINTS FOR FUTURE APPLICATIONS OF THE 4.0D® LEADERSHIP DEVELOPMENT MODEL -- THE 4.0D® LEADERSHIP ASSESSMENT PROTOCOL -- CONCLUDING REMARKS -- REFERENCES.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Leadership; Electronic books